2010
DOI: 10.1677/joe-09-0370
|View full text |Cite
|
Sign up to set email alerts
|

Phenylmethimazole blocks palmitate-mediated induction of inflammatory cytokine pathways in 3T3L1 adipocytes and RAW 264.7 macrophages

Abstract: Visceral adipocytes and associated macrophages produce and release excessive amounts of biologically active inflammatory cytokines via the portal and systemic vascular system, which induce insulin resistance in insulin target tissues such as fat, liver, and muscle. Free fatty acids (FFAs) absorbed via the portal system or released from adipocytes also induce insulin resistance. In this report, we show that phenylmethimazole (C10) blocks basal IL6 and leptin production as well as basal Socs-3 expression in full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 52 publications
7
55
0
Order By: Relevance
“…As shown in Fig. 5B , ( 39 ), and monocyte chemotactic factors, such as serum amyloid A-3 (SAA3) and monocyte chemotactic protein-1 (MCP-1) ( 27 ). However, LA (18:2), the all-cis isomer of CLA and a polyunsaturated fatty acid, does not exert proinfl ammatory or chemotactic effects on adipocytes ( 27 ).…”
Section: E12z-cla Is Taken Up By Mitochondria and Induces Mitochonmentioning
confidence: 94%
“…As shown in Fig. 5B , ( 39 ), and monocyte chemotactic factors, such as serum amyloid A-3 (SAA3) and monocyte chemotactic protein-1 (MCP-1) ( 27 ). However, LA (18:2), the all-cis isomer of CLA and a polyunsaturated fatty acid, does not exert proinfl ammatory or chemotactic effects on adipocytes ( 27 ).…”
Section: E12z-cla Is Taken Up By Mitochondria and Induces Mitochonmentioning
confidence: 94%
“…Our group has identified phenylmethimazole (C10), an inhibitor of pathologic TLR3 signaling/expression, and shown that C10, by virtue of inhibiting the TLR3/Wnt5a pathway is significantly efficacious in in-vitro and in-vivo models of different cancers and auto-immune diseases [1,2,32,33]. Accordingly, in this study, we sought to further investigate the effects of C10 on human breast Figure 4: Combination of tamoxifen and C10 significantly inhibits MCF-7 cell viability/growth over Tamoxifen or C10 alone.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, a key risk factor for NIDDM, is associated with chronic inflammation and the release of inflammatory mediators such as TNF-α from adipose tissue; these inflammatory components may subsequently reduce insulin signaling and insulin-evoked glucose uptake into skeletal muscle, and may also damage insulin-producing pancreatic ÎČ cells (3)(4)(5)(6)11,12,(43)(44)(45)(46). As observed, TNF-α interferes with insulin receptor downstream signaling by phosphorylating IRS-1 at serine 307, resulting in reduced PI3K/Akt activity and GLUT4 translocation (32,33,(47)(48)(49).…”
Section: A B C Dmentioning
confidence: 99%
“…Increasing evidence suggests that this pathway is a target of multiple metabolic signals and inflammatory cytokines associated with obesity (8,9). This pathway is also considered to represent a key risk factor in the development of NIDDM, including its actions upon FFAs, tumor necrosis factor α (TNF-α) and the pro-inflammatory interleukins IL-1ÎČ and IL-6 (10)(11)(12). Amongst other effects, these factors cause aberrant phosphorylation and dephosphorylation of InsR, IRS and Akt; this reduces the efficacy of insulin signaling, including insulin-evoked glucose transport (4,6,7,10,11).…”
Section: Introductionmentioning
confidence: 99%